Real-Time Fluorescence Imaging Using Indocyanine Green to Assess Therapeutic Effects of Near-Infrared Photoimmunotherapy in Tumor Model Mice - Adrian Rosenberg; Daiki Fujimura MD; Ryuhei Okada MD, PhD; Aki Furusawa PhD; Fuyuki Inagaki MD, PhD; Hiroaki Wakiyama MD, PhD; Takuya Kato MD, PhD; Peter L. Choyke MD; Hisataka Kobayashi MD, PhD (Molecular Imaging)
Background: Near-infrared photoimmunotherapy (NIR-PIT) is a cancer therapy that causes an increase in tumor perfusion, a phenomenon termed the super-enhanced permeability and retention effect. Currently, in vivo treatment efficacy of NIR-PIT is observable days after treatment, but monitoring would be improved by more acute detection of intratumor change. Fluorescence imaging may detect increased tumor perfusion immediately after treatment. Methods: In the first experiment, athymic nude mouse models bearing unilateral subcutaneous flank tumors were treated with either NIR-PIT or laser therapy only. In the second experiment, mice bearing bilateral flank tumors were treated with NIR-PIT only on the left-sided tumor. In both groups, immediately after treatment, indocyanine green was injected at different doses intravenously, and mice were monitored with the Shimadzu LIGHTVISION fluorescence imaging system for 1 hour. Results: Tumor-to-background ratio of fluorescence intensity increased over the 60 minutes of monitoring in treated mice but did not vary significantly in control mice. Tumor-to-background ratio was highest in the 1 mg kg −1 and 0.3 mg kg −1 doses. In mice with bilateral tumors, tumor-to-untreated tumor ratio increased similarly. Conclusions: Acute changes in tumor perfusion after NIR-PIT can be detected by real-time fluorescence imaging.